ASSESSMENT OF WATER QUALITY ANALYSIS USING PHYSICO-CHEMICAL PARAMETERS: A CASE STUDY OF BHIMA RIVER IN DAUND TAHSIL, PUNE DISTRICT, MAHARASHTRA. - SV, PATIL; PS, PATIL; BV, TAMHANKAR; GB, KOLEKAR (Innovare Journal of Sciences, 2020)
Objective: Our objective is to examine the previous and current physical and chemical properties of the water in Bhima river in the study area as well as to assess the change in physical and chemical properties of the study area. Materials and Methods: The physico-chemical characteristics of Bhima river water in Daund Tahsil (Pune district) have been studied. The stretch of Bhima river in Daund Tahsil is extending downstream from Dahitane to Malthan. Bhima River was assessed at three various stations in terms of critical pollution parameters in the year 2010-11 and 2011-12. Three sampling stations viz., Station A-near Dahitane (Towards the West side), Station B-near Rahu (in the middle), and Station C-near Daund (towards East side) were established for the collection of water samples during April, 2011 to March, 2012. The water quality parameters namely transparency, colour, (transparent-very turbid), turbidity, total dissolved solids pH ,dissolved oxygen, free carbon dioxide, total alkalinity, Biochemical Oxygen Demand, Chemical Oxygen Demand, total hardness, chloride, nitrate, nitrite, sulphate, phosphate , silicate, sodium, potassium, Calcium and Magnesium reflects on the nature of the river in the study area. Results: On the basis of various parameters studied it was found that the rivers receive industrial effluents from various industries, which are situated on the bank of river, along with the heavy loads of agriculture run off. Conclusion: The conclusion also deals with community response about Bhima river out of the many problems perceived by the river bank residents, the priority problem observed by maximum is that of the mosquitoes and habitants, Agriculture, including commercial livestock and poultry farming. is the source of many organic and inorganic pollutants in surface waters and ground water. Hence the river water quality is needed to be improved